2018
DOI: 10.33314/jnhrc.v16i3.1629
|View full text |Cite
|
Sign up to set email alerts
|

Profile of Neurosurgical Patients in a Tertiary Level Intensive Care Unit in Nepal

Abstract: Background: Neurosurgery has developed as a separate specialty and neurosurgical patients are some of the most common admitted in the intensive care unit. The objective of the study was to study the profile of neurosurgical patients admitted in level III mixed, medical-surgical intensive care unit in a tertiary level teaching hospital in Nepal with the view to identify the causes of intensive care unit admission, types of neurosurgery performed, outcome of the patients, in terms of intensive care unit stay, me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Among the 55 included quantitative studies on stroke patients in Nepal, 19 were cross-sectional studies [ 10 28 ], 17 were retrospective [ 29 45 ], and 17 were prospective cohort studies [ 46 – 62 ]. Two case-control studies were present [ 63 , 64 ], while no randomized trials were found.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Among the 55 included quantitative studies on stroke patients in Nepal, 19 were cross-sectional studies [ 10 28 ], 17 were retrospective [ 29 45 ], and 17 were prospective cohort studies [ 46 – 62 ]. Two case-control studies were present [ 63 , 64 ], while no randomized trials were found.…”
Section: Resultsmentioning
confidence: 99%
“…All 55 studies were hospital-based and were conducted in the tertiary health sector. Of the 55 studies in stroke patients, majority (n = 26) were done in Kathmandu valley [ 12 , 13 , 15 , 16 , 19 , 22 , 27 29 , 31 , 33 , 34 , 41 – 45 , 49 – 52 , 54 , 55 , 59 , 61 , 64 ], followed by Sunsari (n = 7) [ 18 , 30 , 40 , 53 , 56 , 60 , 63 ], Chitwan (n = 6) [ 21 , 25 , 26 , 47 , 48 , 57 ] and Morang (n = 6) [ 24 , 32 , 36 , 46 , 58 , 62 ], which represent Central and Eastern region of Nepal. Only three studies were done in Nepalgunj, the Mid-western part of Nepal [ 11 , 23 , 39 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Neurotrauma was most common in our study which is similar [7][8][9][10][11][12] to other studies. Mortality in traumatic brain injury patient was 3.22% while in other studies it varied from 10.5% to [13][14][15][16] 30%. This difference may be due to early intervention by a neurosurgeon, the presence of neurointensivist, different geographical conditions, and a small group of trauma patients in our study.…”
Section: Discussionmentioning
confidence: 98%